Conserving the Past as a Foundation for the Future : China-World Bank Partnership on Cultural Heritage Conservation - Ebbe, Katrinka; Licciardi, Guido; Baeumler, Axel (World Bank, Washington, DC, 2014)
The rich cultural heritage of China is an essential touchstone of its collective identity. The country's archaeological sites, historic architecture, expressive arts, cultural landscapes, and ethnic diversity also are treasured around the world. Despite their importance, China's cultural assets are under tremendous pressure due to the country's rapid development, particularly its rapid urbanization. Moreover, rising incomes and mobility have significantly increased domestic tourism, leading to the overdevelopment and deterioration of cultural heritage sites. However, many of China's government officials, conservationists, and community groups have recognized these threats and, over the past several decades, have worked tirelessly to protect their country's cultural heritage. Based on the 12 projects developed under this partnership, this report presents an overview of the project approaches and experiences, takes stock of the challenges, extracts initial lessons learned, and identifies new directions and challenges ahead. The principal audience of the report is national, provincial, and municipal decision-makers engaged in conserving China's cultural heritage. This report also is intended to be of relevance to World Bank staff and those in the international community who wish to gain an overview of the projects conserving cultural heritage in China that have received World Bank financing.